Formation of legal awareness of professional competence as a component of pharmaceutical workers in the European Union (Czech experience) - I. M. Alyeksyeyeva; M. S. Ponomarenko; O. G. Aleksyeyev; A .S. Solovyov; Yu. M. Grygoruk (Zaporozhye State Medical University, 2016)
The chosen topic is relevant due to the proclamation of vector of Ukraine's accession to the EU on the state level. This defines modernization of social and economic life in a single internal space. The key to successful solution of this global goal is the ability to take over and meet the high standards of social and economic model of the European Union. Aim. To study the problem of Ukraine's education transformation in connection with the entry to the European educational space. To study the experience of countries that have already passed this way, to analyze the advantages and features that distinguish modern European education policy. Methods and results. Through such research methods as a comparative and analytical study demonstrated the usefulness and application of the experience of the Czech Republic. In the Czech Republic teaching of legal disciplines at the Faculty of Pharmacy is carried out in accordance with the requirements of the Bologna process, but at the same time taking into account the features and capabilities of a particular educational institution. Conclusion. Most knowledge of the legal subject meets Ukrainian medical (pharmaceutical) universities. In the study of discipline "Pharmaceutical Law" focuses on the issues of legal regulation of drugs trafficking, the legal status of pharmaceutical workers, legal liability. Until recently, special attention to the European Union pharmaceutical legislation was not given.